2005
DOI: 10.1073/pnas.0500215102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the protein–protein interfaces in the p53–DNA crystal structures: Towards elucidation of the biological interface

Abstract: p53, the tumor suppressor protein, functions as a dimer of dimers. However, how the tetramer binds to the DNA is still an open question. In the crystal structure, three copies of the p53 monomers (containing chains A, B, and C) were crystallized with the DNAconsensus element. Although the structure provides crucial data on the p53-DNA contacts, the active oligomeric state is unclear because the two dimeric (A-B and B-C) interfaces present in the crystal cannot both exist in the tetramer. Here, we address the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
4
31
0
1
Order By: Relevance
“…Ma et al (20) obtained that, helix 1 residues of monomer B (R181, C182) forms hydrogen bonding with several residues in monomer A (V172, R174, R175, G244) and S185 of monomer B also interacts with T211 of monomer A. These findings map into our suggested dimerization interface region.…”
Section: Dimerssupporting
confidence: 53%
See 2 more Smart Citations
“…Ma et al (20) obtained that, helix 1 residues of monomer B (R181, C182) forms hydrogen bonding with several residues in monomer A (V172, R174, R175, G244) and S185 of monomer B also interacts with T211 of monomer A. These findings map into our suggested dimerization interface region.…”
Section: Dimerssupporting
confidence: 53%
“…In their experimental work, Jiao et al (43) reported observations of dynamic interactions of p53 with DNA including continuous association/dissociation and sliding. Ma et al (20) proposed models for p53 dimer binding to DNA including one that is a sliding mechanism. However, no distinction was made in any of these models between the monomers A, B, or C with respect to their interactions with the DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific ways of association between p53 and DNA and between p53 monomers are supported by several experiments (24 -27). Alternatively, p53 core domain dimerization interface in a crystal structure was also examined to explore their biological relevance (28). Overall, there are little experimental data with respect to the association between the p53 dimers.…”
mentioning
confidence: 99%
“…The DBD of p53 has been well characterized structurally by x-ray crystallography 2,48,49 NMR 42 and computational studies. [50][51][52][53][54][55][56][57] The core domain consists of a central β-sandwich that serves as a basic scaffold, and the DNA binding surface is composed of two large loops L2 and L3 that are held together by a zinc ion and a loop-sheet-helix motif (Fig. 1).…”
mentioning
confidence: 99%